Pelatihan Pembelajaran STEAM berbasis Deep learning untuk Kurikulum Nasional Bagi Guru SD - Ramadhani, Dini; Harahap, Hanif; Rafli, Muhammad Febri; Kenedi, Ary Kiswanto; Sahudra, Tengku Muhammad; Mardin, Asna; Yuliyanti, Yuna; Auliya, Arif Arbi (Jurnal Pengabdian Masyarakat (ABDIRA), 2025)
This community service program aimed to improve the capacity of elementary school teachers in designing and implementing STEAM-based deep learning as part of preparation for the National Curriculum. The program involved 60 teachers from Gugus IV Muda Sedia, Aceh Tamiang, through conceptual training, lesson planning workshops, classroom simulations, and mentoring. Results showed an average competence increase of 69.5%, particularly in integrating STEAM components and higher-order thinking into thematic lesson plans. Classroom observations indicated improved student engagement and learning quality. The activity produced teaching materials, teacher learning communities, and enhanced readiness for curriculum implementation. This model has proven effective and is recommended for replication in other regions.